Providing optimum nitrogen, phosphorus and potassium levels to oil palm as a strategy to combat ganoderma disease infection - Mohidin, Hasmah (2016)
Basal stem rot (BSR) of oil palm caused by Ganoderma boninense, has caused a serious economic impact to the oil palm industry. The BSR affects oil palms at all ages, are spreading to greater area yearly with increasing occurrence in peat soils. Nitrogen (N), phosphorus (P), and potassium (K) nutrition play a critical role in oil palm growth and are known to give beneficial effects on BSR disease control. Plants with optimum nutritional status have the highest resistance to pests and diseases. Therefore, it is important to determine these N, P and K optimum nutrient values to promote overall palm health and provide better protection against Ganoderma disease. This study investigated the optimum concentrations of N, P2O5 and K2O in solution culture (soilless condition) followed by peat soil medium at nursery conditions for dura (D) × pisifera (P) oil palm progeny. These optimum values were adopted and formulated in various levels of N, P, and K nutrition as treatments for three months prior to challenge with G. boninense to assess their effect in relation to Ganoderma incidence and severity on oil palm seedlings grown on peat soil. Subsequently, their effect on nutritional and biochemical traits were then evaluated. Under Hoagland’s solution culture, the optimum levels of N, P2O5 and K2O were found at 100, 90 and 300 mg/L, respectively, at pH 5.5 ± 0.1 of 6.5 months, gave significant growth traits, nutrient uptake in plant tissues and biomass accumulation. On peat soil condition, the best nutrients concentrations N, P2O5 and K2O of 21.72, 21.72 and 40.04 g/plant, respectively, for growth improvement at pH 4.3 ± 0.2, of 16.5 months. N, P2O5 and K2O indicated significant difference (p<0.5) in term of dry biomass accumulation, nutrient concentration and partitioning in tissues at N2, P2, K3 levels. Pathological data revealed the single nutrient deficiency (low N, low K and low P) at 12.16, 12.16 and 22.26 g/plant gave negative effects and were highly infected with Ganoderma. Treatment low N was the most severely infected at the roots, stem boles and leaves with the lowest dry biomass accumulation. Generally, a positive correlation was observed at G. boninense inoculated palm roots for enzymes activity; namely, β-1,3-glucanase PAL, POX, and chitinase, which revealed higher activities (p< 0.5) suggesting their roles in induced defense related mechanism. All the enzyme activities ranked in ascending order were as followed : T5 > T2 > T10 > T8 > T6. In conclusion, optimum N and P nutrient with high K at application of N, P2O5 and K2O, 17.37, 17.37 and 41.34 g/plant, respectively, exhibited a better growth and promoted better protection against BSR for almost all the pathological parameters assessed. However, N, P and K treatments had provide fair protection by delaying G. boninense infection up to 6 month after inoculation but after and beyond this period, they seem to lose their protecting effect. The results could be useful for developing new strategies with proper nutrition, which may effectively reduce Ganoderma incidence and severity grown in peat soil.